The elements of teaching - Banner, James M., Jr., 1935- (Yale University Press, 1997)
What are the characteristics of a great teacher? What qualities of mind and spirit are necessary to help others acquire the knowledge through which they can understand and live a good life? In this book, James Banner and Harold Cannon draw on many years of experience to set forth the intellectual, moral, and emotional capacities that they believe the best teachers must possess. Their book is an inspiring guide to current and future schoolteachers and to college and.